R & D and Internal Finance: A Panel Study of Small Firms in High-Tech Industries - Himmelberg, Charles P.; Petersen, Bruce C. (The Review of Economics and Statistics, 1994)
Charles P. Himmelberg, Bruce C. Petersen, R & D and Internal Finance: A Panel Study of Small Firms in High-Tech Industries, The Review of Economics and Statistics, Vol. 76, No. 1 (Feb., 1994), pp. 38-51